Strategi Guru Bimbingan Konseling Untuk Meningkatkan Manajemen Waktu Siswa Di SMP Negeri 1 Baitussalam - Amalia, Vina Chaira; Khaira, Wanty (Program Studi Bimbingan dan Konseling, 2024)
This research aims to determine the strategies implemented by Guidance Counseling teachers at SMP Negeri 1 Baitussalam in improving students' time management skills. Good time management is expected to help students achieve a balance between academic assignments, extracurricular activities and personal time. This research uses a qualitative approach, where data is collected through direct observation, in-depth interviews with guidance and counseling teachers, students, homeroom teachers, and parents, as well as analysis of related documents such as schedules and guidance materials used. The research results show that the strategies implemented by guidance and counseling teachers include the use of individual guidance approaches and group guidance. The individual approach taken by guidance and counseling teachers, where students are guided to create a daily schedule and determine priorities, helps students plan their time in a more structured manner. Group tutoring sessions provide an opportunity for students to share experiences and learn from their peers about how to manage time. Apart from that, this research also found that the role of parents is very important in supporting the implementation of time management. Parents who are involved in accompanying their children in creating and adhering to study schedules report increased time discipline in students. However, obstacles faced in implementing this strategy include diverting students' attention to social media and other non-academic activities. Therefore, regular eval___uations and additional strategies are needed to overcome external distractions that affect student concentration